Penerapan Regresi Linier Untuk Prediksi Jumlah Kasus Covid-19 di Provinsi Riau - Vina Vamilina; Mustakim Mustakim (STMIK Budi Darma, 2021)
Covid-19 or 2019 corona desease 2019 was first discovered in wuhan China in 2019, to this day the corona virus case continues worldwide. In Indonesia the covid-19 deployment case is not yet complete. One of the areas affected by the pandemic was the riau province. The covid 19 in the province of riau was itself quite high, even being designated as a red zone by the covid-19 task force. Governments continue to seek to reduce the spread of the virus, but one is by conducting a central government guide to vaccination. The purpose of this research is to predict the success of governments in vaccination. Data processing is prepocessing data and validating, then predictions are made. The result of this research is that in the next 1 month the forecast will drop. This is due to an 8.1 % drop in mortality and an 88.7 % rise in mortality. This means that the efforts of riau's provincial government in suppressing covid-9 cases with the vaccination movement have been successful